Origin and fate of surface drift in the oceanic convergence zones of the eastern Pacific. Issue 7 (6th April 2016) - Maes, Christophe; Blanke, Bruno; Martinez, Elodie
Abstract: This study investigates the structure and intensity of the surface pathways connecting to and from the central areas of the large‐scale convergence regions of the eastern Pacific Ocean. Surface waters are traced with numerical Lagrangian particles transported in the velocity field of three different ocean models with horizontal resolutions that range from ¼° to 1/32°. The connections resulting from the large‐scale convergent Ekman dynamics agree qualitatively but are strongly modulated by eddy variability that introduces meridional asymmetry in the amplitude of transport. Lagrangian forward‐in‐time integrations are used to analyze the fate of particles originating from the central regions of the convergence zones and highlight specific outflows not yet reported for the southeastern Pacific when using the currents at the highest resolutions (1/12° and 1/32°). The meridional scales of these outflows are comparable to the characteristic width of the fine‐scale striation of mean currents. Key Points: Lagrangian circulation associated with the large‐scale surface convergence zones in the eastern Pacific Highlighting escape pathways from the center of the convergence zones, with short meridional scales Importance of eddy‐like variability in structuring the large‐scale circulation in a Lagrangian framework